2017
DOI: 10.1103/physreve.96.062502
|View full text |Cite
|
Sign up to set email alerts
|

Topology effects on nonaffine behavior of semiflexible fiber networks

Abstract: Filamentous semiflexible networks define the mechanical and physical properties of many materials such as cytoskeleton. In the absence of a distinct unit-cell, Mikado fiber network model is the most commonly used algorithm for representing the microstructure of these networks in numerical models. Nevertheless, certain types of filamentous structures such as collagenous tissues, at early stages of their development, are assembled by growth of individual fibers from random nucleation sites. In this work, we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…There exists a strain-softening response for low volume fraction gels in which the normalized differential modulus strictly decreases to values less than 1. This strain softening response has been also observed experimentally and numerically in soft gels of different nature and under various loading conditions as well as systems whose microstructure is fibrillar such as polymer fiber networks [7,10,15,[21][22][23][24][25][26]. Similar to the SRG model, the variation of the normalized shear stiffness is significant at the lowest volume fraction φ = 0.05 and becomes less significant with increasing the volume fraction.…”
supporting
confidence: 60%
“…There exists a strain-softening response for low volume fraction gels in which the normalized differential modulus strictly decreases to values less than 1. This strain softening response has been also observed experimentally and numerically in soft gels of different nature and under various loading conditions as well as systems whose microstructure is fibrillar such as polymer fiber networks [7,10,15,[21][22][23][24][25][26]. Similar to the SRG model, the variation of the normalized shear stiffness is significant at the lowest volume fraction φ = 0.05 and becomes less significant with increasing the volume fraction.…”
supporting
confidence: 60%
“…The degree of non-affinity was defined as 29 , 31 where is the total number of nodes in the structure, is the local displacement of the i th node of the multi-material structure, and is the corresponding displacement of the i th node of a corresponding single-material lattice structure (Fig. 1 d).…”
Section: Methodsmentioning
confidence: 99%
“…Non-affine deformation can be characterized in terms of a degree of non-affinity ( ) or non-affine correlation functions 14 , 29 , 30 . The degree of non-affinity is a scalar parameter that depends on the length scale 31 and applied strain 15 , 19 , 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the mechanical response of random networks is a function of their architecture and mechanical properties of their fibrous constituents (7)(8)(9)(10)(11)(12)(13)(14)(15). Furthermore, the specific architecture of random networks has been shown to have significant influence on certain aspects of their mechanical response (16,17). Biological networks often appear either as 1) cross-linked (z % 4) networks in which fibers are interconnected by cross-linking proteins or as 2) branched (z % 3) networks in which the fibers are split into other fibers at the branching points (18).…”
Section: Introductionmentioning
confidence: 99%